Compliance of Scaffolder Workers in using Full Body Harness through Rewards and Punishment as Intervening Variable - Noviyanti, Noviyanti; Utami, Leni; Pani, Dionisius; Rizky, Muhammad (Journal La Medihealtico, 2025)
In the context of occupational safety, compliance refers to the adherence to safety protocols designed to protect workers from various risks and hazards. A high level of compliance is crucial, particularly in high-risk sectors such as construction, where violations of safety procedures can lead to fatal accidents. This study aims to examine the extent to which scaffolding workers comply with the use of personal protective equipment (PPE), specifically the full body harness, through the application of rewards and punishments. A mixed methods approach was employed, combining quantitative analysis using SEM-PLS with qualitative insights obtained from interviews. The findings reveal that two variables had no statistically significant effect: compliance on the use of full body harness (p-value = 0.992 > α = 0.05) and rewards on punishment (p-value = 0.887 > α = 0.05). However, four variables showed statistically significant relationships: compliance on punishment, motivation on punishment, punishment on the use of full body harness, and rewards on the use of full body harness (p-value < α = 0.05). Furthermore, all indirect relationships involving the use of PPE through punishment were found to be insignificant. These results suggest that companies should develop more comprehensive strategies, policies, and standard operating procedures (SOPs), and ensure consistent communication and socialization of safety practices across all operational activities.